Regional Variations in Lobe-wise Micrometrical Parameters of the Porcine Liver from Jammu Region - Singh, Haneet; Sasan, Jasvinder Singh; Suri, Shalini; Sarma, Kamal; Charkraborty, Dibyendu (International Journal of Bio-resource and Stress Management, 2026)
The present study was conducted from January, 2025 to August, 2025 at the Division of Veterinary Anatomy, F.V.Sc and A.H, SKUAST-Jammu, R.S., Pura, Jammu (181102), India to generate detailed quantitative histomorphometric data on the hepatic microarchitecture of the pig liver and to evaluate regional and lobar variations. Liver samples were collected and processed using standard histological techniques, and various structural parameters of the hepatic tissue were measured to assess microanatomical differences among different lobes and regions of the liver. The capsule showed minor regional variations, being consistently thickest in the middle region, with significant variation observed only in the left lateral lobe. Hepatic lobule dimensions demonstrated both regional and lobar variation, with the left lateral lobe exhibiting significantly larger lobules. Central vein diameter varied significantly in the right and left lateral lobes, whereas inter-central vein distance showed no significant differences among lobes. Hepatocyte size and nuclear diameter were consistently greater in the periportal region compared with the centrilobular region, indicating zonal heterogeneity within hepatic lobules. Inter-lobular septa was thickest in the right lateral lobe, while sinusoidal diameters were generally larger in the centrilobular region, particularly in the left medial and left lateral lobes. Overall, the study highlighted distinct lobar and zonal histomorphometric variations in the pig liver, suggesting functional heterogeneity among hepatic lobes and providing baseline reference data for comparative anatomy and experimental research.